2005
DOI: 10.1007/s11270-005-1297-3
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Schoenoplectus californicus in a Constructed Wetland System Receiving Copper Contaminated Wastewater

Abstract: Functional roles of Schoenoplectus californicus, giant bulrush, were evaluated in an 3.2 ha (8-acre) constructed wetland treatment system receiving copper-contaminated water. The constructed wetland used in this research was designed to decrease bioavailable copper concentrations in a wastestream and eliminate associated toxicity to downstream biota by exploiting the thermodynamic processes responsible for copper speciation. This was achieved by integrating carbon, sulfur and copper biogeochemical cycles. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…Therefore even if plant uptake contributed to dissolved metals removal, it is likely not responsible for the noticed improved outlet EMCs. Several other researchers have identified that plant uptake wasn't a dominant process responsible for metal removal in wetlands or FTWs (Murray-Gulde et al, 2005;Kadlec and Wallace, 2009;Sekomo et al, 2011;Tanner and Headley, 2011).…”
Section: Plantsmentioning
confidence: 99%
“…Therefore even if plant uptake contributed to dissolved metals removal, it is likely not responsible for the noticed improved outlet EMCs. Several other researchers have identified that plant uptake wasn't a dominant process responsible for metal removal in wetlands or FTWs (Murray-Gulde et al, 2005;Kadlec and Wallace, 2009;Sekomo et al, 2011;Tanner and Headley, 2011).…”
Section: Plantsmentioning
confidence: 99%
“…Uncontaminated plants were also harvested from on-site nursery wetland cells to serve as controls. Plants were rinsed with deionized water to remove sediment, and separated into roots, submerged shoots (from roots to water surface), emerged shoots, and seeds (Murray-Gulde et al 2005). Adsorbed Hg, Se, and As were measured by separately rinsing submerged shoots and roots with 15% trace metal grade nitric acid.…”
Section: Macrophyte Harvest and Analysismentioning
confidence: 99%
“…Thus, reducing conditions and high organic matter content seem to be essential for the formation of metal sulfides by sulfate reduction (Debusk et al, 1996). Organic matter in wetlands can also promote microbial sulfide production by providing a carbon source for sulfate-reducing microorganisms (Murray-Gulde et al, 2005;Du Laing et al, 2009). Culture experiments with sulfate reducing microorganisms from wetland sediments demonstrated the potential for microbial activity to remove metals from solution while simultaneously producing sulfide (Webb et al, 1998) whereas laboratory-based experiments demonstrated ZnS precipitates formed in the presence of sulfate-reducing bacteria from solutions containing dissolved zinc and sulfate (Peltier et al, 2011).…”
Section: Introductionmentioning
confidence: 99%